Fish hosts of the freshwater mussel Unio foucauldianus Pallary, 1936 - Benaissa, H. (2019)
The life cycle of Unio foucauldianus Pallary, 1936, a critically endangered freshwater mussel species (Bivalvia: Unionida), includes a parasitic phase using fish as hosts. Therefore, to develop more efficient conservation strategies it is essential to know which are the suitable fish hosts of U. foucauldianus. In this study, two approaches were used to assess the fish hosts of U. foucauldianus: the determination of infestation rates of fishes under natural conditions through monthly sampling (from January to June) in the Laabid River (Oum Rbia basin) and the N'Fis River (Tensift basin), and artificial infestation in laboratory trials using fish species from both rivers. The natural infestation of fish was detected from February to June, with a peak in May. Fully metamorphosed juveniles were only detected in native fish species, i.e. Luciobarbus ksibi (Boulenger, 1905), Carasobarbus fritschii (Gunther, 1874), Luciobarbus zayanensis Doadrio, Casal-lopez & Yahyaoui, 2016, Labeobarbus maroccanus (Gunther, 1874), and Luciobarbus magniatlantis (Pellegrin, 1919). The two non-native fish species used do not function as effective hosts. Given the increasing human pressure on native fish species in the Mediterranean biodiversity hotspot, including the increased number of non-native fish introductions, urgent conservation measures are discussed for this and other freshwater mussel species.